Nanopharmaceutics: Part I—Clinical Trials Legislation and Good Manufacturing Practices (GMP) of Nanotherapeutics in the EU - Souto, Eliana B. (Pharmaceutics, 2020)
The latest advances in pharmaceutical technology are leading to the development of cutting edged approaches to produce what is now known as the “Holy Grail” of medicine—nanopharmaceutics. Over the latest decade, the pharmaceutical industry has made important contributions to the scale up of these new products. To ensure their quality, efficacy, and safety for human use, clinical trials are mandatory. Yet, regulation regarding nanopharmaceuticals is still limited with a set of guidelines being recently released with respect to compliance with quality and safety. For the coming years, updates on regulatory issues about nanopharmaceuticals and their use in clinical settings are expected. The use of nanopharmaceuticals in clinical trials depends on the approval of the production methods and assurance of the quality of the final product by implementation and verification of the good manufacturing practices (GMP). This review addresses the available legislation on nanopharmaceuticals within the European Union (EU), the GMP that should be followed for their production, and the current challenges encountered in clinical trials of these new formulations. The singular properties of nanopharmaceuticals over their bulk counterparts are associated with their size, matrix composition, and surface properties. To understand their relevance, four main clinical trial guidelines, namely, for intravenous iron-based nanopharmaceuticals, liposomal-based nanopharmaceuticals, block copolymer micelle-based nanopharmaceuticals, and related to surface coating requirements, are described here.